The Role of Context in the Evolution of a Serial Entrepreneur - Bechtold, David J.; Khandekar, Rajendra; Melnick, Adam (American Journal of Management, 2021)
Entrepreneurial research often focuses on the psychological traits of the entrepreneur but rarely on the notion that under certain circumstances entrepreneurship may be equally driven by external factors beyond the founder's control. This paper looks at the 40-year history of a serial entrepreneur and identifies five types of business ventures driven by contextual factors and the personal attributes of the entrepreneur. These five types are the “advised” venture, the “safe harbor” venture, the “accidental” venture, the “greener grass” venture, and the “passion” venture. The paper closes with a call for future research to include situational context in defining what creates and motivates entrepreneurs.